2010
DOI: 10.1007/s00442-010-1647-8
|View full text |Cite
|
Sign up to set email alerts
|

Predator dietary response to prey density variation and consequences for cestode transmission

Abstract: The functional response of predators to prey density variations has previously been investigated in order to understand predation patterns. However, the consequences of functional response on parasite transmission remain largely unexplored. The rodents Microtus arvalis and Arvicola terrestris are the main prey of the red fox Vulpes vulpes in eastern France. These species are intermediate and definitive hosts of the cestode Echinococcus multilocularis. We explored the dietary and contamination responses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 39 publications
0
35
0
2
Order By: Relevance
“…This place is located in the historical area of higher endemicity of Western Europe, and the average parasite prevalence in fox populations ranged from 20% to 65% (Raoul, Deplazes et al, 2001). Based on the copro-ELISA diagnostic on 1252 faeces collected in the field, Raoul et al (2010) showed that E. multilocularis infection in foxes was asymptotically related to both A. scherman and M. arvalis relative density in the field, suggesting a non-linear parasitic response: infection rose quickly up to a plateau that may be partly attributed to immunity mechanisms regulating infection level. In the Slovak Republic, 3096 red foxes were collected in the entire country between 2000 and 2004 and analysed for E. multilocularis infection using the sedimentation and counting technique (Miterpakova et al, 2006).…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 99%
See 2 more Smart Citations
“…This place is located in the historical area of higher endemicity of Western Europe, and the average parasite prevalence in fox populations ranged from 20% to 65% (Raoul, Deplazes et al, 2001). Based on the copro-ELISA diagnostic on 1252 faeces collected in the field, Raoul et al (2010) showed that E. multilocularis infection in foxes was asymptotically related to both A. scherman and M. arvalis relative density in the field, suggesting a non-linear parasitic response: infection rose quickly up to a plateau that may be partly attributed to immunity mechanisms regulating infection level. In the Slovak Republic, 3096 red foxes were collected in the entire country between 2000 and 2004 and analysed for E. multilocularis infection using the sedimentation and counting technique (Miterpakova et al, 2006).…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 99%
“…The existence of at least two density-dependent mechanisms acting on the control of the parasite transmission dynamics is described: one is based on the variations in the availability of resources including intermediate hosts (Rausch, 1995;Saitoh and Takahashi, 1998;Miterpakova et al, 2006;Tanner et al, 2006;Hegglin et al, 2007;Guislain et al, 2008;Robardet et al, 2008;Raoul et al, 2010;Stien et al, 2010;Wang et al, 2010;Liccioli et al, 2014), and the other is based on the variations in the density of the definitive host and in their faeces distribution (Ewald, 1993;Raoul et al, 2003;Guislain et al, 2007;Wang et al, 2010). However, we are clearly missing data to predict under which conditions the control of E. multilocularis transmission switches from being dominated by intermediate host density to being dominated by definitive host density, and vice-versa, in space and/or in time.…”
Section: Synthesis and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to phases of large population densities where the biomass of the total population of intermediate host can reach several tens of kilograms per ha. During those periods, fox definitive hosts feed almost exclusively on those prey populations that are easy to access and are more likely to ingest infected small mammals even when prevalence is low (Raoul et al 2010). These factors foster transmission (Giraudoux et al 2002) and human exposure risk (Viel et al 1999), the latter possibly via dogs feeding on abundant reservoirs of small mammal intermediate hosts close to towns, villages and rural settlements.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological studies assessing the temporal and spatial factors affecting the prevalence of E. multilocularis in wild canids often rely on the analysis of fecal samples (e.g., Nonaka et al 1998;Raoul et al 2010). In order to provide reliable estimates of parasite prevalence and understand E. multilocularis transmission ecology, it becomes crucial to address limitations related to PCR testing of fecal samples as diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%